(untitled) (Bangladesh Journal of Medical Science, 2021)
The presence of metaplastic ossification within a atypical lipomatous tumour /well differentiated Liposarcoma (ALT/WDLPS) is a rare occurrence. We report a case ALT/WDLPS with unusual extensive metaplastic bone formation in a 30 years female who complained of swelling in the right shoulder for the past one and a half years. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.197-199